2020
DOI: 10.1111/gcb.15126
|View full text |Cite
|
Sign up to set email alerts
|

Coral reef resilience to thermal stress in the Eastern Tropical Pacific

Abstract: Coral reefs worldwide are threatened by thermal stress caused by climate change. Especially devastating periods of coral loss frequently occur during El Niño‐Southern Oscillation (ENSO) events originating in the Eastern Tropical Pacific (ETP). El Niño‐induced thermal stress is considered the primary threat to ETP coral reefs. An increase in the frequency and intensity of ENSO events predicted in the coming decades threatens a pan‐tropical collapse of coral reefs. During the 1982–1983 El Niño, most reefs in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 66 publications
2
57
0
4
Order By: Relevance
“…An investigation of the Great Barrier Reef (GBR) demonstrated such memory in the mass coral bleaching that occurred in 2016 and 2017 (Hughes et al 2019). Memory can play an ancillary role as an ecosystem acclimatizes and develops resilience when subjected to recurring climate extremes where adaptation for coral reefs can occur even at the genetic level (Thomas and Palumbi 2017;Romero-Torres et al 2020;Carballo-Bolaños et al 2020;Mumby and van Woesik 2014;Sully et al 2019;Jurriaans and Hoogenboom 2019;Fine et al 2019;Davidson 2019). The importance of climate memory was, in fact, underscored as being crucial in determining tipping points or critical transitions in climate-sensitive systems (van der Bolt et al 2018 ;Turner et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…An investigation of the Great Barrier Reef (GBR) demonstrated such memory in the mass coral bleaching that occurred in 2016 and 2017 (Hughes et al 2019). Memory can play an ancillary role as an ecosystem acclimatizes and develops resilience when subjected to recurring climate extremes where adaptation for coral reefs can occur even at the genetic level (Thomas and Palumbi 2017;Romero-Torres et al 2020;Carballo-Bolaños et al 2020;Mumby and van Woesik 2014;Sully et al 2019;Jurriaans and Hoogenboom 2019;Fine et al 2019;Davidson 2019). The importance of climate memory was, in fact, underscored as being crucial in determining tipping points or critical transitions in climate-sensitive systems (van der Bolt et al 2018 ;Turner et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…After the 1998 bleaching event, more than 90% of hard corals died (Bianchi et al, 2003(Bianchi et al, , 2006, and it took 16 years for reefs to recover the pre-bleaching values of live hard coral cover (Morri et al, 2015). Such a recovery was consistent with that observed in the eastern tropical Pacific Ocean (Romero-Torres et al, 2020), but was surprisingly slow as compared to the fast coral cover recovery observed in the neighboring Chagos Archipelago (Sheppard et al, 2008) and in other remote Indian Ocean locations with similar oceanographic conditions (Gilmour et al, 2013). All these latter studies concerned nearly uninhabited islands; on the contrary, the Maldives are experiencing a still moderate but nevertheless continuously increasing level of human pressure because of population increase, coastal development, and tourism intensification (Jaleel, 2013;Nepote et al, 2016).…”
Section: Discussionmentioning
confidence: 55%
“…Long-term trends in coral coverage from this region, which have remained very stable over the past 3 decades, are atypical compared to most tropical reefs which have suffered persistent declines (Hughes et al 2017;Romero-Torres et al 2020). Such distinct trends in the tropical Eastern Pacific could be caused by adaption of corals there to highly variable thermal regimes (Romero-Torres et al 2020).…”
Section: Global and Regional Scalesmentioning
confidence: 96%
“…To construct a global coral bleaching model based on environmental covariates, predictions should account for spatial and temporal dependencies. For example, corals in certain geographic regions are likely to respond to heat stress with higher levels of coral bleaching (e.g., areas influenced by the El Niño Southern Oscillation) (Howells et al 2016;Romero-Torres et al 2020) and are likely to change through time due to coral adaptation and assemblage turnover (Dziedzic et al 2019;Gouezo et al 2019). From a statistical standpoint, spatiotemporal uncertainties in the bleaching-environment relationship must be accounted for to ensure that bleaching predictions are not just artefacts of spatial or temporal patterns in unmeasured variables.…”
Section: Introductionmentioning
confidence: 99%